Analisis Perkembangan Berpikir Kreatif Siswa dalam Menyelesaikan Masalah Matematika yang Melibatkan Pengetahuan Awal - Nasrullah (Al Asma: Journal of Islamic Education, 2024)
This study aims to analyze the development of students' creative thinking skills in solving mathematical problems, particularly in the context of flat geometry. The research was conducted at SMP Buq’atun Mubarakah, involving two eighth-grade students as subjects. A qualitative descriptive method was used, with data collected through written tests and interviews to understand the students' thinking processes. Data were analyzed using descriptive and thematic analysis techniques, evaluating students' answers based on indicators of creative thinking skills, such as fluency, flexibility, originality, and elaboration. The results indicate that students can generally understand problems but still face difficulties in applying mathematical concepts, especially in measurements and the perimeter of flat shapes. Students tend to make mistakes in interpreting and solving more complex problems, indicating a need to enhance their creative thinking skills. The implications of this study highlight the importance of strong instructional support and teaching methods that encourage exploration, the use of varied strategies, and technology integration to improve students' creative thinking abilities.